Climate-induced disaster events and migration decisions of flood-prone communities of Punjab, Pakistan; an application of choice experiments approach - Dilshad Ahmad; Anjum Razzaq; Abur Rauf; Muhammad Afzal (Climatic Change, 2026)

Integrating crowdsourced geospatial intelligence and urban morphology for urban waterlogging risk mapping in Karachi, Pakistan - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Yinghai Li; Chengshuai Liu; Junaid Abdul Wahid; Jiali Guo; Xiaotao Shi; Gul-e-Zehra Soomro (Climatic Change, 2026)

Modeling future CO2 trajectories in fast-growing Asian economies: synergizing deep learning and shared socioeconomic pathways - Bijoy Mitra; Mohammed Sakib Uddin; Farzana Jamal; Khaled Mahmud; Syed Masiur Rahman; Mohammad Shahedur Rahman; Muhammad Muhitur Rahman (Climatic Change, 2026)

A scoping review of climate vulnerability indicators: implications for neighborhood-level vulnerability - Muhammad Faisal Shehzad; Joonsoo Sean Lyeo; Nabil Bleibel; Sarah R. Haines; Nicholas D. Spence; Helen Stopps (Climatic Change, 2026)

Correction to: Sea level rise impacts on residential real estate value in Hawai’i - Muhammad Talal Khan; Nori Tarui; Conrad Newfield; Makena Coffman (Climatic Change, 2025)

Sea level rise impacts on residential real estate value in Hawaiʻi - Muhammad Talal Khan; Nori Tarui; Conrad Newfield; Makena Coffman (Climatic Change, 2025)
This paper examines the impact of sea level rise (SLR) exposure on residential property values in Hawaiʻi by employing a repeat sales methodology on coastal properties transacted between 2000 and 2022. Our analysis reveals that properties exposed to a projected 3 ft of SLR appreciate by 0.8% less annually than unexposed properties. This depreciation effect is particularly pronounced on Oʻahu (-1.4% annually) and Hawaiʻi Island (-1.1% annually). The discount is in part explained by local buyers, with properties they purchase incurring a significantly higher annual penalty compared to those acquired by non-local buyers. Seawalls are associated with higher home appreciation rates; however, they do not offset the penalty associated with SLR exposure. Our work provides new evidence on the forward-looking capitalization of climate change exposure into housing markets, demonstrating that buyer origin—potentially representing differing beliefs or knowledge of risk—has a significant influence.

Climate change adjustment factor on rainfall depths in river basins of Khyber Pakhtunkhwa, Pakistan - Muhammad Umar (Climatic Change, 2025)

Advancing energy-related climate mitigation technologies in arctic region: the impact of green finance and critical mineral resources - Muhammad Anas; Wei Zhang; Talal H. Alsabhan; Liaqat Ali; Jie Han (Climatic Change, 2025)

Addressing knowledge gaps on emerging issues in weather and climate extreme events: a systematic review - Kamil Muhammad Kafi; Zakiah Ponrahono; Aliyu Salisu Barau (Climatic Change, 2024)

Understanding the role of green finance and renewable energy consumption for sustainable development in ACI economies - Muhammad Awais Baloch; Danish; Zubeyde Senturk Ulucak (Climatic Change, 2023)

Climate-induced shifts in irrigation water demand and supply during sensitive crop growth phases in South Asia - Qurat-ul-Ain Ahmad; Eddy Moors; Hester Biemans; Nuzba Shaheen; Ilyas Masih; Muhammad Zia ur Rahman Hashmi (Climatic Change, 2023)
This study investigated the shifts in irrigation water demand and supply of the major staple and water-intensive crops (wheat and rice) in the Indus, Ganges and Brahmaputra (IGB) river basins of South Asia under the combined impacts of climate change and socio-economic development during the period 1981–2100. It explores irrigation water usage during climate-sensitive crop growth phases (i.e. vegetative and reproductive which required ~ 60% of the total seasonal (sowing to harvest) water demand), which is supposed to be crucial for long-term integrated crop water management. A hydrology vegetation model Lund Potsdam Jena Managed Land is forced with an ensemble of eight downscaled (5 arc-min) global climate model’s using the RCP (Representative concentration pathways) -SSP (Shared socio-economic pathways) framework, i.e. RCP4.5-SSP1 and RCP8.5-SSP3. To investigate phase-specific crop water projections, trend analysis is performed. It shows a significant ( p <0.001) increase in irrigation water demand during the vegetative phase of wheat (6 mm) and reproductive phase of rice (26 mm) and a decrease during the reproductive phase of wheat (13 mm) and vegetative phase of rice (11 mm) in selected study sites. The large decrease in projected irrigation demand for wheat can be explained by a shortening of the growing season length as a result of rising temperatures and increased precipitation. Whereas, an increase in irrigation demand for rice is a combined effect of higher temperatures and less precipitation during the reproductive phase in the region. At the same time, irrigation supply by surface water and groundwater is likely to change in future due to warmer and drier growing periods, causing a significant increase in groundwater irrigation, mainly for rice. Our major research findings show the importance of crop water assessments during the sensitive crop growth phases of wheat and rice which vary in space and time. Including crop phase-specific, climate impact assessments of regional and global projection will help improve the region’s existing crop-water management strategies and adaptation practices.

CO2 emissions in BRICS countries: what role can environmental regulation and financial development play? - Muhammad Awais Baloch; Danish (Climatic Change, 2022)

Comparison of two model calibration approaches and their influence on future projections under climate change in the Upper Indus Basin - Muhammad Fraz Ismail; Bibi S. Naz; Michel Wortmann; Markus Disse; Laura C. Bowling; Wolfgang Bogacki (Climatic Change, 2020)
This study performs a comparison of two model calibration/validation approaches and their influence on future hydrological projections under climate change by employing two climate scenarios (RCP2.6 and 8.5) projected by four global climate models. Two hydrological models (HMs), snowmelt runoff model + glaciers and variable infiltration capacity model coupled with a glacier model, were used to simulate streamflow in the highly snow and glacier melt–driven Upper Indus Basin. In the first (conventional) calibration approach, the models were calibrated only at the basin outlet, while in the second (enhanced) approach intermediate gauges, different climate conditions and glacier mass balance were considered. Using the conventional and enhanced calibration approaches, the monthly Nash-Sutcliffe Efficiency (NSE) for both HMs ranged from 0.71 to 0.93 and 0.79 to 0.90 in the calibration, while 0.57–0.92 and 0.54–0.83 in the validation periods, respectively. For the future impact assessment, comparison of differences based on the two calibration/validation methods at the annual scale (i.e. 2011–2099) shows small to moderate differences of up to 10%, whereas differences at the monthly scale reached up to 19% in the cold months (i.e. October–March) for the far future period. Comparison of sources of uncertainty using analysis of variance showed that the contribution of HM parameter uncertainty to the overall uncertainty is becoming very small by the end of the century using the enhanced approach. This indicates that enhanced approach could potentially help to reduce uncertainties in the hydrological projections when compared to the conventional calibration approach.

Projection of vegetation impacts on future droughts over West Africa using a coupled RegCM-CLM-CN-DV - Muhammad Shafqat Mehboob; Yeonjoo Kim; Jaehyeong Lee; Myoung-Jin Um; Amir Erfanian; Guiling Wang (Climatic Change, 2020)

Climate change impacts and adaptations for wheat employing multiple climate and crop modelsin Pakistan - Jamshad Hussain; Tasneem Khaliq; Senthold Asseng; Umer Saeed; Ashfaq Ahmad; Burhan Ahmad; Ishfaq Ahmad; Muhammad Fahad; Muhammad Awais; Asmat Ullah; Gerrit Hoogenboom (Climatic Change, 2020)

A multi-proxy reconstruction of spatial and temporal variations in Asian summer temperatures over the last millennium - Feng Shi; Quansheng Ge; Bao Yang; Jianping Li; Fengmei Yang; Fredrik Charpentier Ljungqvist; Olga Solomina; Takeshi Nakatsuka; Ninglian Wang; Sen Zhao; Chenxi Xu; Keyan Fang; et al. (Climatic Change, 2015)

Future change in the frequency of warm and cold spells over Pakistan simulated by the PRECIS regional climate model - Siraj ul Islam; Nadia Rehman; Muhammad Munir Sheikh (Climatic Change, 2009)